2021
DOI: 10.5811/westjem.2021.7.52826
|View full text |Cite|
|
Sign up to set email alerts
|

Gender-based Barriers in the Advancement of Women Leaders in Emergency Medicine: A Multi-institutional Qualitative Study

Abstract: Introduction: Leadership positions occupied by women within academic emergency medicine have remained stagnant despite increasing numbers of women with faculty appointments. We distributed a multi-institutional survey to women faculty and residents to evaluate categorical characteristics contributing to success and differences between the two groups. Methods: An institutional review board-approved electronic survey was distributed to women faculty and residents at eight institutions and were completed anonymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…These findings are in keeping with previous studies that have shown that the greatest levels of attrition in commitment to academia for females occurs during residency 48 with increasing levels of attrition continuing up each faculty rank position to the title of full professor 49 . A recent multi‐institutional survey sent to female EM faculty and residents found that 68.4% of respondents experienced gender discrimination as they progressed throughout their academic careers and that this continues to be a significant barrier to female advancement within academia in EM 50 . While these differences are striking, future research investigating the direct impacts of discordant and critical feedback on female resident professional development and methods to address these gender differences within assessment feedback is needed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in keeping with previous studies that have shown that the greatest levels of attrition in commitment to academia for females occurs during residency 48 with increasing levels of attrition continuing up each faculty rank position to the title of full professor 49 . A recent multi‐institutional survey sent to female EM faculty and residents found that 68.4% of respondents experienced gender discrimination as they progressed throughout their academic careers and that this continues to be a significant barrier to female advancement within academia in EM 50 . While these differences are striking, future research investigating the direct impacts of discordant and critical feedback on female resident professional development and methods to address these gender differences within assessment feedback is needed.…”
Section: Discussionsupporting
confidence: 83%
“…49 A recent multi-institutional survey sent to female EM faculty and residents found that 68.4% of respondents experienced gender discrimination as they progressed throughout their academic careers and that this continues to be a significant barrier to female advancement within academia in EM. 50 While these differences are striking, future research investigating the direct impacts of discordant and critical feedback on female resident professional development and methods to address these gender differences within assessment feedback is needed.…”
Section: Qualitative Assessment Datamentioning
confidence: 99%
“…This even occurs for men leaders, who, like our high-ranking participants, may find that "silence is pervasive in organizations due to the widely shared belief that speaking up about sensitive issues is futile or even dangerous." 22,23 While the perceptions of GBD among women who are targeted are well-documented, 1,3,7 our findings add to the literature by addressing the perceptions of GBD among an advantaged group, men leaders, who bear witness to it. Witnessing GBD produced negative emotional responses, including feelings of shame, guilt, disbelief, and anger, in these men participants.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 67%
“…4 In EM, women report high rates of GBD: 52.6% of women in EM report being sexually harassed, 25% report genderbased disrespect, and 9.5% report at least 1 encounter of sexual assault by a colleague or supervisor during their career. 1,[5][6][7] Women physicians are more likely to experience GBD than men, particularly from patients, other physicians, or nursing staff. 1,8 Despite GBD's prevalence, women physicians report only approximately 5% of incidents, often due to the belief that nothing will be done or changed or the fear of retaliation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation